Technology and medicinal properties of cultivating lavender growth - Ibrahim Shahlo Ibrahimna. (Zien Journals, 2023)
This article outlines the cultivation technology, biology, importance and chemical composition of lavender growth in public administration
Keywords: Advanced technology; vegetation; medicinal properties